FACTORS INFLUENCING EDUCATIONAL WASTAGE AMONG GIRLS IN SECONDARY SCHOOLS IN KENYA: A CASE OF KISII CENTRAL DISTRICT - Mosigisi, Matage Justus; Wanbua, Kyalo Benjamin; Saina, Shandrack (European Scientific Journal, ESJ, 2015)
The purpose of this study was to examine the factors influencing wastage among girls in secondary schools in Kisii Central district. Generally it looked into the factors that force girls to drop out of school or repeat grades. The objectives that were used to guide this study were to; establish the influence of school related factors on the wastage rate among girls at secondary level in Kisii central district, establish the influence of economic factors on wastage among girls in secondary schools in Kisii Central district, investigate the influence of cultural factors on wastage among girls in secondary schools in Kisii central district , and finally establish the influence of social factors on wastage rate among girls in secondary level in Kisii central district. The study was both qualitative and quantitative in nature. Descriptive survey research design was used in conducting the study. This study was based on the production function theory as expressed by Psacharapoulos and Wood hall (1985). Stratified random sampling was used to select 22 secondary schools which were either public mixed or public girl’s schools. This formed 35% of the total 63 public mixed and public girls’ schools in the study area. The respondents were all head teachers and one form three class master in each selected school. Form three students of the selected schools also participated. All the above respondents were purposively sampled into the study. A total of 399 respondents participated. Data was collected using questionnaires and interview schedules. Piloting of the study was conducted in two schools in the neighbouring Gucha district. The collected data was analyzed using descriptive and inferential statistics. The inferential statistics used was chi-squire. From the findings it was found out that economic factors like poverty at household level, cultural factors such as pregnancy and marriages were responsible for dropout among girls. Also, school related factors like school examination regulations and social factors such as provision of sanitary towels were found to affect girls’ education negatively. It is therefore hoped that the findings and recommendations of this study will be useful to educational planners and other educational stakeholders in solving the problem of wastage among girls in secondary schools in Kenya.